IMPLEMENTASI SUPERVISI AKADEMIK DALAM MENINGKATKAN KINERJA GURU - Zulfakar, Zulfakar; Lian, Bukman; Fitria, Happy (Graduate Program Magister Manajemen Pendidikan, 2020)
This study aimed at determining how the performance of elementary school teachers can be improved through academic supervision conducted by the principal of the elementary school. This research was conducted in 16 Public Elementary School Gelumbang. The research method used is a qualitative method with a descriptive approach. Data collection tools using interviews, observation, documentation and literature review. The results of the study stated that the process of academic supervision was carried out by the principal through several stages, namely 1) planning of academic supervision activities; 2) conducting academic supervision; 3) feedback the results of academic supervision; and 4) follow up on the results of academic supervision. The tools for evaluating are in the form of supervision instruments, namely 1) instruments for evaluating the administration of learning devices; 2) instruments for RPP assessment; 3) instruments for evaluating learning implementation; 4) instruments for evaluating learning evaluations; instrument for follow-up; instrument for evaluating teacher performance. The academic supervision can improve the performance of teachers in 16 Public Elementary School Gelumbang.